Driving Corporate Sustainability Through A Green HRM, Employee Engagement, and Green Innovation at PT GHP - Puspitasari, Dian Noviati; Aulia, Irfan Noviandy (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Achieving sustainable economic growth while reducing environmental damage presents a significant challenge in the era of globalization and technological advancements. As primary contributors to greenhouse gas emissions, industries hold a pivotal position in advancing global initiatives aimed at meeting Sustainable Development Goals (SDGs). This study investigates the influence of Green Human Resource Management (GHRM) and Employee Engagement on Corporate Sustainability, with Green Innovation serving as a mediating variable on PT GHP. In this study, the researcher used a quantitative research type. The research model was analyzed using partial least squares structural equation modeling (PLS-SEM) with the Smart-PLS software, based on a sample of 56 respondents. The findings of this study reveal that GHRM and Employee Engagement have a positive and significant influence on Corporate Sustainability and Green Innovation. Furthermore, Green Innovation mediates the relationship between GHRM and Corporate Sustainability, while its mediating role on Employee Engagement is not statistically significant.